(untitled) (Journal of the College of Languages (JCL), 2022)
The present study stresses two of the most significant aspects of linguistic approach: Pragmatics” and the “Speech Act Theory”, revealing its importance and the stages and levels of development through Hebrew language’s speech acts analysis including (political speech, the Holy Bible, Hebrew stories). Chronologically, Pragmatics has always been the center of linguists’ interests due to its importance in linguistic decryptions, particularly, through “Speech Act Theory” that has been initiated and developed by the most prominent philosophers and linguistics. The present study discloses that “Speech Act Theory” is the backbone of Pragmatics. This is due to the fact that its scope doesn’t only include the language message sender, but rather (the sender, the receiver, the environment, the context, and the speaker’s social standards and attitude of the language). Reflecting the social culture as well as the society standards and morals, “Speech Act Theory” can effortlessly facilitate grasping the message of the speaker’s intentions by the message receiver. תקציר המחקר הזה שופך אור על שני מושגים עיקריים בחקר הלשון "הפרגמטיקה" ו"פעולת־הדיבור" ועל תודלותיהם ושלבי התפתחותם דרך ניתוח פעולות הדיבור בלשון העברית בכל רבדיה ושלביה (השיח הפוליטי, התנ’’ך, סיפורים עבריים). הפרגמטיקה עברה שלבים חשובים במרוצת הזמן. בימינו החוקרים התעניינו בגישה הזאת ובמיוחד בתחום התקשורת הלשוני משום שהיא מסייעת אותם בפענח המסרים בין השוחחים, באמצעות התיאוריה המרכזית בחקר הפרגמטיקה "תיאורית פעולת הדיבור", שהופיעה והתפתחה על ידי קבוצה של פילוסופים ובלשנים מפורסמים בחקר הלשוני. ממצאי המחקר מגלים כי תיאורית פעולת הדיבור היא הבת הבכורה של הפרגמטיקה, משום שהיא אינה מתעניינת אך ורק בדיבור המוען, אלא היא עברה לממדים אחרים כגון (מקבל הפעולה, הסביבה שמתרחשת בה הפעולה, ההקשר הלשוני והחוץ לשוני, נורמות החברה, מעמד הדובר והשומע... וכן הלאה). באמצעות התיאוריה הזאת אנו יכולים להבנת כוונותיו של הדובר כלפי הנמען, בנוסף לכך היא משקפת את התרבות החברתית של חברה מסוימת ואת נורמות המבנים החברתיים והמוסריים שלה.